Hypothetical endogenous SIV-like antigens in Mauritian cynomolgus macaques - Li, Hongzhao (Bioinformation, 2018)
Simian immunodeficiency virus (SIV) infection of Mauritian cynomolgus macaques (MCMs) is an increasingly important nonhuman primate model for HIV vaccine research. We previously reported that in MCMs anti-SIV antibodies can be naturally developed without exogenous infection or vaccination, and that a vaccine targeting SIV protease cleavage sites (PCS) can cross-induce antibodies to non-PCS SIV antigens. We speculate that this is potentially caused by the existence of endogenous SIV-like antigens. External stimuli (such as environmental factors and vaccination) may induce expression of endogenous SIV-like antigens to elicit these antibodies. Database and mass spectrometry analyses were conducted to search for such antigens. We identified endogenous SIV-like DNA sequences in cynomolgus macaque genome and non-PCS peptide homologous to SIV Env protein in PBMCs of a PCS-vaccinated monkey. Our preliminary insights suggest that endogenous SIV-like antigens may be one of the possible reasons for the natural and cross-inducible SIV antibodies in MCMs.